The Use of Free Space Measurement Method to Identify Dielectric Constant of Rice Husks - Basuki Rahmat, Mohammad; Zuhri Arfianto, Afif; Rakhmad Handoko, Catur; Setiawan, Edy; Agus Widodo, Hendro; Prasetyo Hidayat, Edy; Mudjiono, Urip; Sidi, Pranowo; Handoko, Lukman; Hamzah, Faiz; Setijadi, Eko; Mauludiyanto, A.; et al. (International Journal of Engineering and Technology, 2018)
An absorber works by reducing wave reflection. Used as an anechoic chamber, an absorber has a very important role. A good absorber material is able to attenuate wave reflection that can affect the performance of a tool being tested. Absorber that is used and mass produced is an absorber made of polyurethane. The alternative material for making an absorber is rice husks. To determine the ability of rice husk as a microwave absorber, a simulation using CST software is needed. Problem arises since the dielectric constant value of the rice husk is unknown. Therefore, it is necessary to test the rice husk absorber board to determine the dielctric constant value. The method used to determine the dielectric constant is free space measurement. The free space measurement method can be explained as: two horn antennas which serve as transmitter and receiver positioned at a certain distance. Both are connected with the Vector Network Analyzer. Rice husk board is placed between the two antennas. The measurement is aimed at gaining reflection loss value and transmission coeficient value. The value is then used to determine the dielectric constant. The result of the test indicate that the constant value is between 3.5 to 3.7Â Â